(untitled) (Research, Society and Development, 2020)
Non-conventional food plants (PANCs) are edible parts of plants that can be easily found in urban and rural environments and that are not usually included in the diet. However, there is little or no use of these vegetables in the daily diet of the population. Therefore, the objective of this work was to demonstrate the great nutritional potential of these plants by establishing aspects related to their nutritional properties, antioxidants and use in food. This study is a bibliographic review. Scientific articles published in the last 5 years on the Scielo, Lilacs, Pubmed and Scienc Direct data platforms were used. The studies showed a great diversity of vegetables with excellent nutritional composition, rich in macronutrients and bioactive compounds that would increase and diversify the diet of the Brazilian population, but which are little or no used due to the lack of knowledge of their nutritional benefits and their employment in food production. As it was seen above, it is suggested that new research can be developed to allow the expansion of the population’s knowledge about PANCs.